ChemInform Abstract: [RuCl2(p‐cymene)2]2 Catalyzed Cross Dehydrogenative Coupling (CDC) toward Xanthone and Fluorenone Analogs Through Intramolecular C—H Bond Functionalization Reaction. Issue 14 (April 2015) - Manna, Sudipta Kumar; Manda, Srinivas Lavanya Kumar; Panda, Gautam
Abstract: The route to biologically active xanthone and fluorenone analogs proceeds smoothly for substrates equipped with electron‐donating substituents, but leads to no reaction or trace amounts of products for substrates with electron‐withdrawing groups.